2007
DOI: 10.1590/s0034-89102007000100010
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of physical activity from adolescence to adulthood: a population-based study

Abstract: OBJECTIVE:To assess the association between regular physical activity in adolescence and leisure-time physical activity in adulthood, with emphasis on gender differences. METHODS:A population-based cross-sectional study was carried out in Pelotas, Southern Brazil, in 2003. A representative sample of households was selected in multiple stages and subjects aged 20-59 years were interviewed. Leisure-time physical activity was evaluated using the International Physical Activity Questionnaire. Data on adolescent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
86
1
61

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(160 citation statements)
references
References 23 publications
10
86
1
61
Order By: Relevance
“…Previous studies have reported a high frequency of ball games among men across ages 14 to 31 years 21) . Dance and gymnastics were more popular with women 15,22) . Our finding supports the previous gender difference in the traditional preferences for specific types of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a high frequency of ball games among men across ages 14 to 31 years 21) . Dance and gymnastics were more popular with women 15,22) . Our finding supports the previous gender difference in the traditional preferences for specific types of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A prática regular de atividade física de intensidade moderada a vigorosa e exercícios de força e alongamento nessa faixa etária podem proporcionar benefícios para a saúde dos jovens, bem como a diminuição de fatores de risco para doenças cardiovasculares, além da melhora da saúde osteomioarticular e mental 2,3 . Ainda, pesquisas mostram que adolescentes fisicamente ativos tendem a se tornar adultos igualmente ativos 4,5 . No entanto, dados da Pesquisa Nacional de Saúde do Escolar (PeNSE) mostraram que mais da metade dos adolescentes brasileiros (57%) não atinge as recomendações mínimas de prática de atividade física para a saúde 6 .…”
Section: Introductionunclassified
“…2 Therefore, the regular practice of physical activity is an important behavior to prevent chronic diseases and it must be promoted during the whole growth and development process so that such behavior become more likely to become a habit in adulthood as has been demonstrated by international 3,4 and Brazilian studies. 5 Adolescents should engage in moderate to vigorous physical activities for at least 60 minutes a day, thus reaching 300 minutes a week. Such activities may be practiced at school or not, either consisting of supervised or unsupervised practice.…”
Section: Introductionmentioning
confidence: 99%